Efek Mediasi Kesulitan Keuangan dalam Mendeteksi Corporate Fraud di Indonesia - Natalis Christian (Universitas Swadaya Gunung Jati, 2022)
AbstractThis study analyzed the mediating effect of financial distress on the research model of the fraud hexagon effect on corporate fraud. The research model in this study was tested using the multiple regression analysis method using 210 companies data collected from companies listed on the Indonesia Stock Exchange during 2015-2019. The originality of this research is to add financial distress as a mediating variable in explaining the effect of fraud hexagon theory on corporate fraud in Indonesia. The results show empirical evidence that financial distress has a significant positive mediating effect in explaining the effect of stimulus on corporate fraud. Financial distress has a significant negative mediating effect in explaining the effect of collusion, opportunity and rationalization on corporate fraud. Financial distress has also been proven to have no mediation effect in explaining the influence of capability and ego on corporate fraud. The test results prove that high financial achievement targets and political connections have lower the risk of experiencing financial distress. Loose supervision and inconsistent implementation of corporate governance can plunge the company into financial distress. These conditions will eventually encourage companies to commit corporate fraud in order to cover up the financial distress they are experiencing.Keywords: Corporate fraud; Financial distress; Fraud hexagon; F-score; Mediating effect Abstrak Penelitian ini menganalisis efek mediasi kesulitan keuangan pada model penelitian pengaruh fraud hexagon terhadap corporate fraud. Model penelitian diuji menggunakan metode analisis regresi berganda dengan data 210 perusahaan yang terdaftar di Bursa Efek Indonesia selama periode 2015-2019. Originalitas penelitian ini adalah menggunakan kesulitan keuangan sebagai variabel mediasi dalam menjelaskan pengaruh teori fraud hexagon terhadap corporate fraud di Indonesia. Hasil penelitian menunjukkan bukti empiris bahwa kesulitan keuangan memiliki efek mediasi positif yang signifikan dalam menjelaskan pengaruh variabel stimulus terhadap corporate fraud. Kesulitan keuangan memiliki efek mediasi negatif yang signifikan dalam menjelaskan pengaruh variabel collusion, opportunity dan rationalization terhadap corporate fraud. Kesulitan keuangan juga terbukti tidak memiliki pengaruh mediasi dalam menjelaskan pengaruh variabel capability and ego terhadap corporate fraud. Hasil pengujian membuktikan bahwa target pencapaian keuangan yang tinggi serta adanya koneksi politik dapat menurunkan resiko perusahaan mengalami kesulitan keuangan. Longgarnya pengawasan dan penerapan tata kelola perusahaan yang tidak konsisten dapat menjerumuskan perusahaan ke dalam kondisi kesulitan keuangan. Kondisi yang mendesak pada akhirnya akan mendorong perusahaan untuk melakukan corporate fraud demi menutupi kondisi kesulitan keuangan yang dialami.Kata Kunci: Kejahatan perusahaan; Kesulitan keuangan; Fraud hexagon; F-score; Efek mediasi